Upper lip profile changes - Hussain A Obaidi; Manar Y Abdul-Qadir (University of Mosul, College of Dentistry, 2007)
Aims: To explore the upper lip thicknesses, height and it's relationship to the esthetic line. Materials and Methods: The studying sample included 48, 41, 50 and 44 individuals of age 11, 12, 13 and 14 years respectively. The subjects were Iraqi individuals of Class I normal occlusion, who live in center of Mosul City. All subjects were radiographed with lateral cephalometric films, these films were traced, the tracing included the upper lip thickness at skeletal points (A-A´ ), upper lip thickness at labrale superius (Ls-Ls´), upper lip height at stromion superior to palatal plane and the upper lip relationship to the esthetic line. All these measurements were measured and then subjected to the statistical analysis. Results: The results were demonstrated that the upper lip thickness (A-A`) and (Ls-Ls`) were only significant increase at 14 year age groups as compared with 11 years age group in males. In female the upper lip thickness was only significant at 13 years group as compared with 11 years age group, while the upper lip relationship to esthetic line showed only significantly greater value at 14 years age group as compared with 13 years age group. Sex variation appeared a significant greater value in male than female for the (Ls-E line) at 11 years age group, (A-A`) and (Ls-E line) at 12 years age group, (Ls-Ls`) at 13 years age group and upper lip height at 14 years age group and upper lip height at 14 years age group. Conclusions: The soft tissue of upper lip profile parameters were increased with increasing age group, and the upper lip significantly larger behind the esthetic line in female than male at 11, 12 and 14 years age groups.